Energy optimization and performance analysis of a novel integrated energy system coupled with solar thermal unit and preheated organic cycle under extended following electric load strategy. (1st June 2023) - Zhang, Han; Han, Zhonghe; Wu, Di; Li, Peng; Li, Peng
Abstract: Integrated energy system (IES) coupled with solar thermal (ST) unit and organic Rankine cycle (ORC), namely ST-ORC-IES, plays a vital role in renewable energy and waste heat utilization. In this paper, a novel ST-ORC-IES is proposed, in which the preheated ORC with higher power output is employed and the diversified utilization of ST unit is realized. Then the extended following electric load strategy is introduced to coordinate electricity generation by considering the output fluctuation of ORC. Finally, an optimization model is constructed to achieve the maximum fossil fuel efficiency on both hourly and annual scales, and a new index is developed to evaluate cost performance. Optimization results show that ST-ORC-IES exhibits better cost performance than reference system, the fossil energy consumption is reduced by 10.89%, while the annual total cost is only increased by 0.77%. The rationale that energy time-varying optimization can improve cost performance is the significant saving of natural gas. In addition, the total electricity output of heat engine and ORC presents an upward trend with the increase of heat engine load, this mechanism enables the collaborative planning for power sources based on the simple principle of basic operation strategy. These findings can provide reference for related research. Highlights: A novel ST-ORC-IES is proposed to realize diversified heat utilization. A new strategy to coordinate the power outputs of prime mover and preheated ORC. A novel evaluation index to reflect the cost performance of proposed system. An optimization model to maximize fossil energy efficiency on two-time scales. The benefits and operation characteristics of ST-ORC-IES are analyzed.